The Influence of High Dietary Energy Sources on Haematological Status and Niacin Treatment of the Rabbits - Ironkwe, M.O.; Oruwari, B.M. (Pakistan Journal of Nutrition, 2011)
Four isonitrogenous diets A-control B-12% palm oil, C-12% groundnut oil and D-33% corn meal were fed to 40 weanling rabbits. The experiment was a Completely Randomized Design (CRD). At the end of the 15th week, blood was collected from 24 of the rabbits through cervical cutting while 16 were treated with niacin for another 8 weeks. The blood was collected to ascertain whether the high dietary energy diets was stressogenic on the rabbits through their blood parameters. The result showed significant (p